Simulation of IoT-Based Temperature and Humidity Conditioning System in Screen House - Wirenda Sekar Ayu; Bowo Yuli Prasetyo (Bandung State Polytechnic (Politeknik Negeri Bandung), 2022)
Nowadays, various problems have arisen in agricultural sector. One of which is the decline in productivity of farmers' crops up to 40% which is caused by non-optimal environmental conditions during the plant growth process. This is certainly a challenge for Indonesian farmers to be able to continue in supplying the country's needs for high quality agricultural products. The challenges faced by Indonesian farmers do not only come from the environmental conditions of plant growth, but the development of Industry 4.0 technology also plays an important role in the development of agricultural sector in Indonesia. In order to adapt to these technological changes, a solution is needed in the form of an integrated agricultural equipment with Industry 4.0 technologies such as the Internet of Things (IoT). One of which is creating an IoT-based control and monitoring system that will be applied to the screen house. In this research, an IoT-based temperature and humidity conditioning system was designed in the screen house. The system design is modeled and tested through simulation on Vensim software. Based on the simulation results of system design, the screen house internal temperature can be controlled or maintained in the optimal temperature range for tomato plant growth, which is 18–24oC with an offside value of ±0.5oC. The heating capacity or heating rate required in this system is 10oC/hour. The cooling capacity or cooling rate generated to compensate the influence of external temperature and heating effect on the screen house internal temperature is 1–1.8oC/hour. The heating and cooling rate values generated in this research are still need to be converted into fan and pump PWM values to be implemented in a fan- pad evaporative cooling system.